PENGAJARAN TUHAN YESUS MENGENAI BERBAHAGIA DALAM MATIUS 5:3-12 - Yohanes Enci Patandean (Sekolah Tinggi Teologi Simpson, 2018)
Yohanes Enci Patandean, Preaching the Lord Jesus to be blessed in Matthew 5: 3-12. This article discusses the preaching of the Lord Jesus concerning of blessing in Matthew 5: 3-12 and analyzed there are three points to be analyzed, that is the understanding of blessing, blessing objects/goals and the reasons why should be blessed. The method that used is descriptive with a qualitative approach to the biblical text, and word analysis methods. In the text of Matthew 5: 3-12, Jesus teaches about blessed which includes the standard of living of the blessed people and the reasons why believers should be blessed. Jesus gives the preaching of blessing which includes the standard of living of a happy person is poor before God; mourning; gentle; hunger and thirst for righteousness; generous; sacred heart; bring peace; persecuted by righteousness; blemished and persecuted for Christ; and slandered all evil. Yohanes Enci Patandean, Pengajaran Yesus Mengenai Berbahagia Dalam Matius 5:3-12. Artikel ini membahas tentang pengajaran Tuhan Yesus mengenai berbahagia dalam Matius 5:3-12 dan dianalisis ada tiga hal pokok yang menjadi analisis yaitu pengertian berbahagia, sasaran/objek berbahagia serta alasan-alasan mengapa harus berbahagia. Metode yang digunakan adalah deskriptif dengan pendekatan kualitatif pada teks Alkitab, dan metode analisis kata. Dalam teks Matius 5:3-12, Yesus memberikan pengajaran mengenai berbahagia yang mencakup standar hidup orang-orang yang berbahagia serta alasan-alasan mengapa orang-orang percaya harus berbahagia.Yesus memberikan pengajaran mengenai berbahagia yang mencakup standar hidup orang-orang yang berbahagia dan standar hidup orang yang berbahagia ialah miskin di hadapan Allah; berdukacita; lemah lembut; lapar dan haus akan kebenaran; murah hatinya; suci hatinya; membawa damai; dianiaya oleh sebab kebenaran; dicela dan dianiaya karena Kristus; difitnahkan segala yang jahat.